Self-Esteem and Sensation Seeking in Online Dating Application’s Users - Putri, Friska Nur Setia; Rinaldi, Martaria Rizky (ANFUSINA: Journal of Psychology, 2024)
The increasing number of online dating application users is an interesting phenomenon, but research in Indonesia that discusses the related psychological aspects is still limited. This study aimed to determine the relationship between self-esteem and sensation seeking in early adulthood users of online dating applications. The subjects of this study were 214 people with characteristics: aged 20 to 34 years who used online dating applications. Data collection for this study used the Sensation Seeking Scale, namely the Zuckerman - Kuhlman - Aluja Personality Questionnaire (ZKA-PQ) with a reliability coefficient of α = 0.84 and the Rosenberg Self-esteem Scale (RSE) with a reliability coefficient of α = 0.753. The study's findings revealed that the self-esteem level was not significantly related to the tendency of sensation seeking in early adult users of online dating applications (rₛ = -0.045, p = 0.252). The results of this non-parametric statistical test failed to reject the null hypothesis, so it can be concluded that the two variables are independent of each other in the population studied.